Kekerasan di Layar: Analisis Simulacra dalam Representasi Anak di Media Online - Elsera, Marisa (Regalia: Jurnal Riset Gender dan Anak, 2024)
The purpose of this study is to describe the form of representation of violence against children through online media. The theory used in this research is Jean Baudrillard's simulacra theory. The research method uses a qualitative method with a literature approach. The results of this study show that exposure to violence in online media affects the representation of violence in children. Finally, children not only represent existing violence but also internalise the images and narratives produced by the media. The process of imitation, image or duplication of the representation of the reality of violence then exceeds the existing reality to form a new reality. Cases of child abuse caused by online media can use online games, social media, films and television to creative activities that children often access. This research also shows that desensitisation occurs in children due to repeated exposure.